Diagnosis of tuberculosis in pleural effusion of lung tumor patients using adenosine deaminase test - Fazmar, Muh. Dinul; Muh. Ilyas; Sudarso, Agus; Bakri, Syakib; Alimuddin, Suriani; Zainuddin, Andi Alfian (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Tuberculosis (TB) remains a global burden and presents challenges both in diagnosis and treatment, primarily when focusing on the association between pleural effusion, lung tumors, and TB. This study aimed to evaluate the efficacy of adenosine deaminase (ADA) as a non-invasive diagnostic tool for TB in pleural effusion among patients with lung tumors. Given the limitations of sputum culture, the study emphasizes the need for standardized diagnostic approaches, particularly in endemic regions such as Indonesia. Methods: The study includes 79 subjects with primary lung tumors and pleural effusion. Sample collection employed consecutive sampling, with pleural fluid samples obtained from hospitalized individuals. Laboratory tests were conducted using the ELISA method. Statistical analysis, using SPSS version 26, employed a descriptive approach to analyze the research data, with a level of statistical significance set at a P value of <0.05. Results: The study established an ADA cut-off of ≥34 IU/L for tuberculosis diagnosis, exhibiting excellent discrimination (AUC: 98.8%) and a sensitivity of 87.5% with 95.8% specificity. The positive and negative predictive values were 70% and 98.55%, respectively. These results support ADA’s efficacy in predicting TB in lung tumor patients with pleural effusion, with considerations for potential biases in comorbid conditions and intensive TB treatment. Conclusions: ADA is a reliable diagnostic marker for TB in lung tumor patients with pleural effusion, underscoring its clinical utility in TB diagnosis. The findings emphasize ADA’s significance in discriminating TB status, offering valuable insights for clinical decision-making in similar patient populations.